A call for revolution : a vision for the future - Bstan- dzin-rgya-mtsho, Dalai Lama XIV, 1935-; Stril-Rever, Sofia (William Morrow, an imprint of HarperCollinsPublishers, 2018)
A Landmark Message from His Holiness the Dalai Lama: Are we ready to hear it? Are we ready to act? "I call on you to confront the challenges of our era by rising up and embarking upon a revolution that has no precedent in human history." This eloquent, urgent manifesto is possibly the most important message the Dalai Lama can give us about the future of our world. It<U+2019>s his rallying cry, full of solutions for our chaotic, aggressive, divided times: no less than A CALL FOR REVOLUTION.